The heart in systemic autoimmune diseases - Atzeni, Fabiola; Doria, A. (Andrea); Nurmohamed, Mike; Pauletto, Paolo, 1947- (Handbook of systemic autoimmune diseases, 2017)
This book provides an overview on the current understanding of major complications relating to the heart and autoimmune diseases. It includes the latest information on the new pathogenetic mechanisms involved, along with clinical manifestations of these important comortbidities. Mortality in autoimmune diseases, in particular, rheumatoid arthritis and SLE, has increased when compared with the general population, due largely to cardiovascular diseases.